Estudio comparativo: disgrafía motriz y el aprendizaje en los estudiantes de segundo año de educación general básica de la Unidad Educativa Inclusiva “Isabel de Godín” y de la Unidad Educativa “Santo Tomás Apóstol” de Riobamba, Chimborazo - Mena Villacis, Tatiana Pamela (2021)
This investigation had as objective, to set an existing correlation among motor dysgraphia and learning abilities, especially on general education second grade parallel “A” students at “Isabel de Godín” and “Santo Tomás Apóstol Inclusive Education Units in Riobamba – Chimborazo”. Motor dysgraphia is a learning process issue on students because it consists on certain hand and arm muscles troubles. It prevents the student from mastering and directing the writing instrument, this causes the child to be unable to write legibly and neatly; therefore, it will also prevent learning to read and write. As a method, a non-experimental investigation design was executed. The kind of investigation for its level or reach is descriptive and correlational, for its objective is basic, for the work place is a field type, the kind of investigation is transversal. The sample was established with 68 second year students of General Basic Education parallel "A" in the referred institutions. Some psychometric tests were used as data collection instruments, like literacy analysis test (TALE) by Josep Toro and Montserrat Cervera for the independent variable and for the dependent variable the psychometric test Child Learning and Development Test by Marta Edwards, Marcela Pardo and Mariel Gómez, in addition to other resources such as the SPSS 23 program for data analysis. It was found that there is a correlation between motor dysgraphia and learning, that is to say, when the student has motor dysgraphia, it looks reflected on learning.